Effect of Drought and Heat Wave on Agricultural Production - Gürkan Yılmaz (Doğal Afetler ve Çevre Dergisi)
As the effects of anthropogenic climate change, the frequency and severity of heat waves and drought are increasing day by day in many parts of the world. Droughts and heat waves are often interrelated disasters. Prolonged heat waves often cause drought to occur and/or exacerbate existing drought. These types of disasters cause great losses and damages especially in agricultural production. In this study; By examining the examples of drought and heat wave disasters in different parts of the world, the effects of these disaster types on agricultural production have been tried to be explained. Within the scope of this study, disaster reports, magazines, books and internet news were examined. According to the data obtained; It was determined that crop production, animal production, natural resources, human capital and economy were negatively affected. It has been observed that especially yield and product loss are experienced in cultivated products. It has been determined that there are situations such as a decrease in the yield of fresh grass in the pasture areas and the disappearance of the pasture areas. Losses in cultivated crops for forage crops and fresh grass in pasture areas cause an increase in feed prices and serious problems in feed supply. The increase in feed prices and the problems experienced in the supply of feed cause yield loss in animal products and a decrease in the number of animals fed. Economically, it has been determined that there are effects such as price increase, production cost increase, and decrease in exports.